Pengaruh Social Media Marketing dan Influencer Marketing terhadap Keputusan Pembelian Produk Deliwafa di Kota Gresik - Septrilia Putri, Alicya Dewi; Zawawi, Abdullah; Zaini, Ahmad Afan (Al-Muzdahir : Jurnal Ekonomi Syariah, 2025)
The ease with which people can access information about a product has given rise to a new shopping system that can be done online. Then, this is used by companies to attract the interest of their potential consumers by utilizing social media as a part of digital marketing, this strategy is also called Social Media Marketing (SMM). One of the social media applications that is currently frequently used is the Tiktok and Instagram applications. The TikTok and Instagram application algorithms are different from other applications, making it easier for people to go viral and be recognized by many people. So, the term influencer emerged as someone who can have an influence on other people. To become a company that can be known to the wider public, a company must have a good brand image so that potential consumers can easily remember what products the brand produces. Referring to this, the question arises of the influence of social media marketing and influencer marketing on purchasing decisions for Deliwafa products in Gresik City. This research used quantitative research with 100 respondents who were followers of the Gresik City branch of the Deliwafa Instagram account who were analyzed using multiple linear regression. Based on the results of data analysis, it is known that social media marketing influences the decision to purchase Deliwafa products in Gresik City, the influencer marketing variabel also has a positive and significant influence on the decision to purchase Deliwafa products in Gresik City